Acute effect of static stretching on the performance and electromyographic activities of the antagonist muscles - Silva, Tamara Karina (2020)
The present study aimed to verify the acute effect of static stretching (SS) of the hamstrings muscles on the mioletric activation (EMGRMS) and strength performance of the antagonist muscle. Twelve men (20.28 ± 1.50 years, 83.35 ± 17.86 kg, 177.28 ± 9.64 cm) experienced in strength training were randomly divided into SS and control groups (GC). For the SS, three repetitions of 30s of static stretching were performed on the hamstrings and then the range of motion (ROM) was assessed. Subsequently, the strength performance and EMGRMS of the vastus lateralis (VL) and vastus medialis (MV) were assessed during the 10-RM test in the extensor chair. The twoway ANOVA found a significant difference in ROM for the main time effect (P = 0.019) and for group x time interaction (P = 0.023), with a significant increase in ROM after stretching (P = 0.013). The number of repetitions ater stretching increased significantly (P = 0.014; 16%) compared to the CG. There was no significant change in EMGRMS os the assessed muscles. The use of static stretching can improve the strength performance of the antagonist musculature.